Numerical Simulation of In Situ Combustion of Oil Shale - Huan Zheng; Weiping Shi; Dali Ding; Chuangye Zhang (Geofluids)
This paper analyzes the process of in situ combustion of oil shale, taking into account the transport and chemical reaction of various components in porous reservoirs. The physical model is presented, including the mass and energy conservation equations and Darcy’s law. The oxidation reactions of oil shale combustion are expressed by adding source terms in the conservation equations. The reaction rate of oxidation satisfies the Arrhenius law. A numerical method is established for calculating in situ combustion, which is simulated numerically, and the results are compared with the available experiment. The profiles of temperature and volume fraction of a few components are presented. The temperature contours show the temperature variation in the combustion tube. It is found that as combustion reaction occurs in the tube, the concentration of oxygen decreases rapidly, while the concentration of carbon dioxide and carbon monoxide increases contrarily. Besides, the combustion front velocity is consistent with the experimental value. Effects of gas injection rate, permeability of the reservoir, initial oil content, and injected oxygen content on the ISC process were investigated in this study. Varying gas injection rate and oxygen content is important in the field test of ISC.